2019
DOI: 10.3389/fimmu.2019.00579
|View full text |Cite
|
Sign up to set email alerts
|

Negative Immunomodulatory Effects of Type 2 Porcine Reproductive and Respiratory Syndrome Virus-Induced Interleukin-1 Receptor Antagonist on Porcine Innate and Adaptive Immune Functions

Abstract: Impaired innate and adaptive immune responses are evidenced throughout the course of PRRSV infection. We previously reported that interleukin-1 receptor antagonist (IL-1Ra) was involved in PRRSV-induced immunosuppression during an early phase of infection. However, the exact mechanism associated with PRRSV-induced IL-1Ra immunomodulation remains unknown. To explore the immunomodulatory properties of PRRSV-induced IL-1Ra on porcine immune functions, monocyte-derived dendritic cells (MoDC) and leukocytes were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…In contrast, piglets fed milk replacer are associated with signi cantly increased concentrations for IL-1ra and IL-8. IL-1 receptor antagonist (IL-1ra) is an anti-in ammatory agent that reduces in ammation by blocking the binding of the agonist receptor ligands 54 . Probably, some properties of the milk replacer composition may be antigenic and supplementary analysis may be useful to detect the degree of immune reactivity against antigens of these products.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, piglets fed milk replacer are associated with signi cantly increased concentrations for IL-1ra and IL-8. IL-1 receptor antagonist (IL-1ra) is an anti-in ammatory agent that reduces in ammation by blocking the binding of the agonist receptor ligands 54 . Probably, some properties of the milk replacer composition may be antigenic and supplementary analysis may be useful to detect the degree of immune reactivity against antigens of these products.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between these two important CD4 + T-cell subsets is crucial for an effective and healthy immune response. The two research groups reported that PRRSV-2 stimulates Tregs [8,10,11,12,46]. Based on those reports, it has been speculated that the PRRSV-2 is shifting that balance of the CD4 T-cell response towards Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…One main characteristic of PRRSV-2 is its ability to actively suppress the host immune response facilitating prolonged viremia, persistence in tissues, and the development of chronic secondary infections associated with PRDC. The following mechanisms of PRRSV-2 immune suppression were reported: The inhibition of NK cell activity and Type I Interferons production in the innate response [3]; the induction of PRRSV-2 specific CD4 + CD25 + regulatory T cells (Tregs) [4,5,6,7,8,9,10,11,12]; and the dysregulation of T-cell development in the neonatal thymus [13]. Ideally for the host, an effective T-cell response to PRRSV-2 would display the characteristics of a strong T-helper type 1 (Th1) response: Early CD4 + Th proliferation and significant production of IFN-γ; the differentiation of PRRSV-reactive Th cells into both, lymph node homing central memory (T CM ) and tissue homing effector memory (T EM ) populations [14]; and the induction of multifunctional memory T cells (T multi ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the induction of Tregs, Nedumpun et al. showed that PRRSV-infected moDCs induced the expression and production of IL-1Ra, which is a natural suppressor of the inflammatory response ( 59 , 60 ). Chen et al.…”
Section: Monocyte- and Bone Marrow-derived Dcs Response To Prrsvmentioning
confidence: 99%
“…In addition to the induction of Tregs, Nedumpun et al showed that PRRSV-infected moDCs induced the expression and production of IL-1Ra, which is a natural suppressor of the inflammatory response (59,60). Chen et al ( 61) demonstrated that the viral N protein and nsp10 enhanced the production of CD83, an inhibitor of DC-mediated T-cell proliferation (62), via activation of NF-KB and Sp1 signaling pathways (61).…”
Section: Monocyte-and Bone Marrow-derived Dcs Response To Prrsvmentioning
confidence: 99%